PENGARUH METODE DISKUSI KELOMPOK TERHADAP PEMAHAMAN KONSEP FISIKA PESERTA DIDIK - Nurfadilah, Nurfadilah; Handayani, Yusri (Universitas Tadulako, 2022)
The effect of the group discussion method on the understanding of physics concepts for students of Class XI IPA SMAN 11 Wajo. This research was conducted to determine the effect of learning with the discussion method on the understanding of physics concepts for class XI students of SMAN 11 Wajo. The population in this study were all students of class XI IPA SMAN 11 WAJO which consisted of 4 classes with a total of 164 students, with the determination of the sample through simple random sampling. After the withdrawal of the class threshold is carried out with the intention of not disturbing the learning process at school too much. Then the class XI IPA2 was chosen for the experimental class and class XI IPA1 for the control class. Collecting data for the assessment of students' understanding of physics concepts using a concept understanding test in the form of an essay given after treatment. Hypothesis testing was carried out by linear regression analysis with SPSS 16 which showed that there was an effect of the group discussion method on the understanding of physics concepts for students of Class XI IPA SMAN 11 Wajo. From this research, it is known that learning with the discussion method provides a new influence for students to further improve the process and understanding of physics concepts